Socio-Ecological Factors Associated with Preventive Behavior - Engdawork, Kibur; Amdework, Ezana; Assefa, Samuel (Brill, 2024)
Understanding factors influencing the adoption of preventive behaviors is crucial in pandemic prevention and control. This study employs the social-ecological model to examine the determinants of preventive actions against COVID-19 in Addis Ababa, Ethiopia. Data from a household survey were analyzed using a linear regression model. The findings indicate a moderate level of preventive behavior adoption among residents. Interpersonal behavior, community norms, and organizational-level factors are identified as significant predictors, while personal and demographic factors have little influence. These results highlight the need for context-specific health interventions, addressing social and structural aspects, to effectively combat COVID-19 in Addis Ababa and similar low- and middle-income settings.
Keywords: COVID-19; Preventive actions; Socio-ecological model; Health intervention; Ethiopia; Middle-income setting